Capital structure management differences in Latin American and US firms after 2008 crisis - Rodrigues, Santiago Valcacer (2017)
Purpose – This paper aims to analyse the capital structure determining factors of Latin American and US corporations after the crisis of 2008, as a means of comparing theoretical assumptions and empirical results in markets of different efficiency levels. Design/methodology/approach – The study sample comprises 1,091 companies belonging to the six largest economies in Latin America plus the USA, in the years 2009 to 2013. The authors performed a regression with data from a balanced overview, which were obtained by using the criterion of minimum weighted square. Findings – The results demonstrated differences in determining factors of capital structure between companies from Latin America and from the USA. The pecking order theory was mostly observed in Latin American companies and the trade-off theory greater was closely aligned with US firms. Originality/value – This research brings new contributions to the issue, once the differences and determinative of the debt profile in companies from different economic contexts are compared.